Dual CRISPR‐Cas9 Cleavage Mediated Gene Excision and Targeted Integration in Yarrowia lipolytica. Issue 9 (11th June 2018) - Gao, Difeng; Smith, Spencer; Spagnuolo, Michael; Rodriguez, Gabriel; Blenner, Mark
Abstract : CRISPR‐Cas9 technology has been successfully applied in Yarrowia lipolytica for targeted genomic editing including gene disruption and integration; however, disruptions by existing methods typically result from small frameshift mutations caused by indels within the coding region, which usually resulted in unnatural protein. In this study, a dual cleavage strategy directed by paired sgRNAs is developed for gene knockout. This method allows fast and robust gene excision, demonstrated on six genes of interest. The targeted regions for excision vary in length from 0.3 kb up to 3.5 kb and contain both non‐coding and coding regions. The majority of the gene excisions are repaired by perfect nonhomologous end‐joining without indel. Based on this dual cleavage system, two targeted markerless integration methods are developed by providing repair templates. While both strategies are effective, homology mediated end joining (HMEJ) based method are twice as efficient as homology recombination (HR) based method. In both cases, dual cleavage leads to similar or improved gene integration efficiencies compared to gene excision without integration. This dual cleavage strategy will be useful for not only generating more predictable and robust gene knockout, but also for efficient targeted markerless integration, and simultaneous knockout and integration in Y. lipolytica . Abstract : A dual cleavage CRISPR‐Cas9 strategy directed by paired sgRNAs is developed for gene knockout, markerless integration, and simultaneous knockout and integration in Yarrowia lipolytica. The homology mediated end joining based method is twice as efficient as homology recombination for simultaneous targeted markerless gene integration and gene knockout.